2014
DOI: 10.5455/2319-2003.ijbcp20140813
|View full text |Cite
|
Sign up to set email alerts
|

Role of pharmaco-epidemiology in psychopharmacology: a study in psychiatric out-patient department of a tertiary care teaching hospital at Dehradun, Uttarakhand

Abstract: INTRODUCTIONPhysicians/medical professionals are continuously exposed to newly introduced drugs that are claimed to be safer and more efficacious. Their utilization and consequences on real-life effectiveness and safety in actual clinical practice need continuous study.1 Rational drug prescribing is defined as the use of the least number of drugs to obtain the best possible effect in the shortest period and at a reasonable cost. Measurement of drug use in health facilities not only describes drug use patterns … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
4
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 3 publications
7
4
0
Order By: Relevance
“…Out of 196 prescriptions analyzed, male-to-female ratio was 1:1.17, correlating with the fact that depression is higher in females, which is consistent with studies by Grover et al, [11] Memon and Patel [12] , and Avanthi et al [13] Majority of patients were in the age group of 30-51 years in both sexes, which is similar to those reported in studies by Dutta et al, [14] Trivedi et al [15] , and Grover et al [11] Pediatric and geriatric groups together constituted less than 10% of our patient population, which is comparable to a previous study. [12] Depression was more common among housewives, which is comparable to a previous study.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Out of 196 prescriptions analyzed, male-to-female ratio was 1:1.17, correlating with the fact that depression is higher in females, which is consistent with studies by Grover et al, [11] Memon and Patel [12] , and Avanthi et al [13] Majority of patients were in the age group of 30-51 years in both sexes, which is similar to those reported in studies by Dutta et al, [14] Trivedi et al [15] , and Grover et al [11] Pediatric and geriatric groups together constituted less than 10% of our patient population, which is comparable to a previous study. [12] Depression was more common among housewives, which is comparable to a previous study.…”
Section: Discussionsupporting
confidence: 88%
“…Trihexyphenidyl was the most common anticholinergic prescribed, similar to previous studies. [14,16,17] Although the frequency of prescribing atypical antipsychotic was higher in our study, yet anticholinergic agents were also prescribed to the patients. Similar observation was made in a study by Ren et al [23] in which when anticholinergic agents were used concomitantly with atypical antipsychotics, patients tend to stay on target drug significantly longer than those who did not use any anticholinergic agents.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…21 The mean age group in our study was 46.84±1.1 years which were comparable with previous studies by Dutta et al and Grover et al where incidence of depression was seen in more commonly in 30-51 years age group. 22,23 More depression patients were seen in rural areas as compared to urban areas in the present study. This was comparable with previous studies by Giel and Harding; Gautam and Kapur where rural background subjects were found to be somatising more than the urban subjects.…”
Section: Discussionmentioning
confidence: 40%